Implementasi Program Rehabilitasi Penyalahgunaan Narkoba Di BNN Kota Tanjungpinang Kepulauan Riau - Rahma Destia; Rumzi Samin; Ramadhani Setiawan (Perkara : Jurnal Ilmu Hukum dan Politik, 2023)
Drug abuse is an extraordinary crime and has reached a very worrying situation and is also being implemented by law enforcement. Drugs are a serious problem that is currently being faced by the State of Indonesia, starting from the local and national environment, this can be seen from the increase in cases of drug arrests which can be revealed to have increased both in terms of the number of users and the number of dealers. The purpose of this study was to determine the implementation of drug use rehabilitation at the National Narcotics Agency in Tanjungpinang. In order to get accurate results select informants, head of BNN, rehabilitation implementers, rehabilitation beneficiaries and the community. This research method is a descriptive research with a qualitative approach. Data collection techniques carried out through observation, interviews, and documentation. This technique uses the theory of Van Metter and Van Horn. Based on the results of this study, the implementation of the drug abuse rehabilitation program at the Tanjungpinang City BNN went well in outpatient and inpatient rehabilitation programs. In the outpatient process there are obstacles. The conclusion from this study is that the implementation of the drug abuse rehabilitation program at the National Narcotics Agency (BNN) in Tanjungpinang City has been running according to the regulations of the National Narcotics Agency of the Republic of Indonesia No. 24 of 2017 concerning Rehabilitation Service Standards for narcotics addicts and victims of narcotics abuse. Suggestions from this study are the need for more attention to the proportion of measures and policy goals, increase human resources and budget, involve related organizations, improve the quality of implementing agents, improve communication, and involve social, economic and political environmental factors.